Platelet-Rich Plasma Provides Superior Clinical Outcomes Without Radiologic Differences in Lateral Epicondylitis: Randomized Controlled Trial - Taha Kizilkurt; Ahmet Serhat Aydin; Taha Furkan Yagci; Ali Ersen; Celal Caner Ercan; Artür Salmaslioglu (Medicina)
Background and Objectives: Lateral epicondylitis, commonly known as tennis elbow, is a prevalent condition characterized by pain and tenderness over the lateral epicondyle. Various treatment options, including corticosteroids, platelet-rich plasma (PRP), and saline injections, are utilized, yet their comparative efficacy remains unclear. Hypothesis: This study hypothesizes that PRP injections result in superior functional and clinical outcomes compared to corticosteroid and saline treatments, as assessed by clinical scoring systems and radiological findings. Materials and Methods: The study enrolled patients aged 18 years and older with pain and tenderness over the lateral epicondyle persisting for at least three months and no prior treatment. Patients with comorbidities affecting the upper extremity were excluded. Fifty-five elbows from 50 patients were randomized into three groups (glucocorticoid, PRP, and saline). Functional outcomes were assessed using the Visual Analog Scale (VAS), Patient-Rated Tennis Elbow Evaluation (PRTEE), and Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire. Radiological evaluations included vascularity and superb microvascular imaging (SMI) indices via ultrasonography before injection and three months post-injection. Results: Fourteen patients were lost to follow-up, leaving 36 patients (36 elbows, 16 males and 20 females; mean age 42.4 ± 6.15 years) for analysis. The glucocorticoid group included 13 elbows, PRP group 14 elbows, and saline group 14 elbows. Baseline functional and radiological scores were similar across groups. At three months, PRP and glucocorticoid groups showed no significant differences in VAS scores (p = 0.7), but PRP outperformed both of the other groups in DASH and PRTEE scores, with the saline group performing the worst (p < 0.001). PRP consistently achieved the best outcomes at both three and six months. Radiological assessments revealed no significant group differences in vascularity or SMI indices (p = 0.3 and p = 0.2, respectively). Conclusions: PRP treatment demonstrated superior functional outcomes in early and mid-term evaluations compared to glucocorticoid and saline. However, ultrasonographic measures of vascularity and SMI did not correlate with functional outcomes. Clinical Relevance: PRP offers a promising treatment option for lateral epicondylitis, with superior functional improvements over other commonly used injections. Radiological assessments of vascularity and SMI may not reliably predict clinical outcomes.